TINJAUAN HUKUM PERKAWINAN DI INDONESIA TERHADAP KONSEP KAFA’AH DALAM HUKUM PERKAWINAN ISLAM - Yudowibowo, Syafrudin (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractIslam basically does not stipulate that a male may only be married to woman whose common thing, both in position, wealth, ethnicity ,etc. Islam doesn’t make rules concerning kafa'ah, but it is people who set them. Islam considers that humans are created equal. No set of people who can not afford not be able to marry, the Arabs should not marry non-Arab people. (Al-Hamdani, 1989: 98)In order to establish and create a family that sakinah mawaddah and rahmah, ulama suggest that there is a balance of harmony, correspondence (there is an element kafa'ah) between the prospective spouses Pasal 2 ayat 1 of Act No. 1 of 1974 when viewed from the principle of equality Kafa'ah concept in religious matters embraced by each bride should be the same even if not explicitly prohibit the State of different religious intermarriage Compilation of Islamic Law Article 61 states that